Кількість та етнічний склад населення Полтавської округи (за матеріалами перепису населення 1926 р.) - Скляр, Володимир Миколайович; Гутник, Марина Валеріївна; Тверитникова, Олена Євгенівна (Національний технічний університет України "Київський політехнічний інститут ім. Ігоря Сікорського", 2022)
Статистичні матеріали переписів населення важливі для дослідження етнічних процесів в Україні. Публікація результатів перепису населення 1926 р. виявилася найповнішою, порівняно з усіма іншими радянськими переписами. Аналіз статистичних матеріалів перепису населення дає змогу визначити етнічний склад населення Полтавщини напередодні демографічної катастрофи 1930-х рр. На основі опрацювання статистичних матеріалів перепису населення 1926 р. підготовлено дві авторські таблиці щодо етнічного складу населення Полтавської округи загалом, її міського та сільського населення, міст окружного та районного підпорядкування, селищ міського типу, а також усіх 24 районів. Нині ці терени входять до складу Полтавської обл., а також частково до Харківської та Сумської обл.

Population census statistics are important in the study of ethnic processes in Ukraine. Publication of the results of the 1926 census proved to be the most complete, in comparison with all other censuses of the Soviet period, which makes it possible to establish the peculiarities of the ethnic composition of the population not only within the regions, that were at that time, but in the individual districts, cities, and urban settlements in the middle of 1920᾽s. The analysis of statistical materials of the census allows us to determine the ethnic composition of the population of Poltava region on the eve of the demographic catastrophe of the 1930᾽s. Based on the compilation of statistical materials from the 1926 census, two authors’ tables were prepared. These tables describe the ethnic composition of the population of the Poltava region as a whole, its urban and rural population, cities of district and district subordination, urban settlements, and all 24 districts. Now, these territories are a part of the Poltava region, and also the parts of the Kharkiv and Sumy regions. The vast majority of Poltava’s population lived in rural areas. Therefore, the level of urbanization of the population of Poltava remained only 13.13 %. The dominant feature of the ethnic composition of the population of the Poltava region was the absolute dominance of the number of Ukrainians in Poltava and in all 24 districts. Ethnic minorities had a predominantly dispersed type of settlement, primarily Jews, Poles, Belarussians, as well as Russians and Germans. Most of the ethnic minorities lived in the regional center, but there they were in the minority among the whole population. Only Russians (5 village councils) and Germans (1 village council) had areas of small-scale settlement. At that time, there were 332 village councils in the territory of the Poltava region, in 326 of them the absolute majority among the whole population were Ukrainians. In 1926, the proportion of Ukrainians among the rural population of Poltava region reached 96.49%, and the share of each of the ethnic minorities remained rather insignificant. The study of the ethnic composition of the population based on the 1926 census of other regions of Ukraine is promising. The availability of statistical materials facilitates the analysis of not only ethnic, but also the linguistic composition of the population. Such studies are important both for ethnology and also for regional history.
The Number and Ethnic Composition of the Poltava District Population (According to the 1926 Census)
Keywords: Полтавська округа; перепис населення; етнічний склад населення; українець; етнічна меншина; Poltava region; 1926 census; ethnic composition; Ukrainians; ethnic minorities